Quantum dissonance in chiral graphene nanoribbons. (15th March 2019) - Tan, Xiao-Dong; Kang, Xiu-Bao; Zhao, Li-Min; Zhang, Jun-Ji; Hao, Hao-Shan
Abstract: Based on the effective spin-ladder model, we study the properties of quantum dissonance ( Q ) between two edge spins in chiral graphene nanoribbons (CGNRs) thermalized with a reservoir at temperature T, and discuss the influences of relative location between two edge spins, ribbon width, temperature, and on-site Coulomb repulsion ( U ) on Q . The results show that Q is widely present in Wannier edge states. For intra-edge coupled spin pairs, quantum entanglement ( E ) is zero, but there still exists considerable value of Q . Interestingly, Q always keeps a constant for entangled edge spin pairs. Considering the thermal effect, it shows that Q always decays with the increasing temperature T, and the decay rate is very sensitive to the intensity of U . Compared Q with E and total quantum correlation (quantum discord, denoted by D ), we conjecture that the quantum correlations for a bipartite Wannier edge state in CGNRs satisfy the relation Q   ⩽   D – E .